KEPATUHAN BEROBAT PENDERITA TUBERKULOSIS PARU DI PUSKESMAS, KOTA JAYAPURA, PROVINSI PAPUA TAHUN 2010 - Felicia Kurniawan; Nelly T. Widjaja; Gevanski H. Maturbongs; Steve F Karundeng; Fransiscus B. Rapa (Atma Jaya Catholic University of Indonesia, 2011)
Background: The prevalence of pulmonary tuberculosis in Indonesia wasranked at the third position, following China and India across the world. The prevalence at Jayapura, the capital city of Papua province was 1.1% above the national prevalence. However, the treatment evaluation carried out in Primary Health Care at Jayapura City in 2008 pointed out that only 58.9% patiens recovered, 25.9% dropped out, 9.8% moved out and 5.4% died. It represented that although Primary Health Care in Jayapura city have been applying Directly Observed Treatment Short-course (DOTS ) program, but still drop out patients remained high.Design: Cross sectional study which was conducted in July 13, 2010 until August 1, 2010.Methods: Seven from nine primary health care at Jayapura city with 104 respondents were involved in this study. Sample was carried out from patients who came to the primary health care on the day of treatment that have beencompromised by each of the institution. The data was analyzed using SPSS 15 and Chi-Square and Fisher exact test.Conclusions: There was a significant relation between home visit and the attitude of health workers which take care of the patients with DOTS program. The suggestion of this study is to maintain or improve home visit activities toincrease the compliance treatment in patients with tuberculosis in primary health care at Jayapura City.